Differentiation among spotted fever group rickettsiae species by analysis of restriction fragment length polymorphism of PCR-amplified DNA. - Eremeeva, M (1994)
Restriction fragment length polymorphism (RFLP) analysis of PCR-amplified genes was used to study spotted fever group (SFG) rickettsiae, extending the previous work of Regnery et al. (R.L. Regnery, C.L. Spruill, and B.D. Plikaytis, J. Bacteriol. 173:1576-1589, 1991). Twenty-six strains of SFG rickettsia were studied, including several recognized species which have never been studied (R. parkeri, R. helvetica, and R. japonica) as well as strains which are not currently classified. Two previously used primer pairs derived from the R. prowazekii citrate syntase gene and the R. rickettsii 190-kDa protein antigen gene were studied, as were primer pairs obtained from the R. rickettsii 120-kDa protein antigen gene. By using three amplifications and three enzyme digestions, it was possible to differentiate between almost all of the known SFG rickettsia species and to differentiate between several strains of the R. conorii complex. Two human pathogens, "R. africae" and the Israeli tick typhus rickettsia, were first separated by using BG-12 pair primer amplification and then RsaI restriction endonuclease digestion. The proposed simplified model of identification may be useful in studying the geographical distributions of SFG rickettsiae.